Effect of Beam Collimation on Patient Dose and Scattered Radiation During Lumbar X-ray: A Phantom Study - Azlinawati, Ali; Nor Azimah, Othman; Ummulwaqiah Maisarah, Mohd Khairudin (Penerbit Universiti Sultan Zainal Abidin, 2020)
Lumbar plain radiography has been one of the most commonly requested procedures in spine evaluation especially for post-operative assessment of lumbar and in ankylosing spondylosis. However, despite of using tight collimation, patient dose resulting from repetitive spinal imaging is a critical issue in determining health consequences. Thus, this study aimed to determine the effect of collimation on patient dose and scattered radiation during lumbar projection. Anteroposterior (AP) and lateral lumbar projections were performed using half-body phantom with three different sizes of beam collimation; minimum (345.6 cm2 ), medium (520.8 cm2 ) and maximum (728cm2 ). Thermo-luminescent dosimeter (TLD) and survey meter were used to measure radiation dose to the phantom and scattered dose respectively. The dose of radiation to the liver, colon and ovaries were significantly increased upon increasing of beam collimation size in AP projection (p < 0.001). The same correlation between radiation dose and beam collimation size was shown on lateral lumbar projection (p < 0.001), except for radiation dose to the colon (p = 0.662). Effective dose and scattered radiation in both AP and lateral lumbar projections were also increased as beam collimation size increased (p < 0.001). In conclusion, radiation dose to the organs (except for colon), effective dose and scattered radiation were directly correlated to the size of beam collimation in both AP and lateral lumbar projections.